Anti-hyperpermeability effect of Malaysian tualang honey on hydrogen peroxide-induced increased vascular permeability - Devasvaran, Kogilavanee (2016)
Vascular hyperpermeability remains the main cause of underlying disorders in myocardial ischemia and atherosclerosis. Tualang Honey (TH) has been used in traditional medicine for decades and proven to possess multiple pharmacological actions. However to date, little is known about the use of TH in anti‐inflammatory activity specifically in endothelial barrier protection. Thus, this study aimed to investigate the effects of TH on H2O2‐induced endothelial hyperpermeability in vitro and supported by an in vivo approach. In order to determine the effect of TH on endothelial hyperpermeability, HUVEC was pre‐treated with pre‐defined noncytotoxic concentration (via cytotoxicity assay) of TH for 4h and then exposed to 0.5mM H2O2. FITC‐dextran was used as a permeability indicator. The supportive in vivo study was the Miles assay, which quantified the extravasation of Evans blue dye in the dorsal skin of balb/c mice. To examine the cells morphological alterations, adherence junction proteins in HUVEC were identified using Fluorescein Phalloidin, caveolin-1 and β‐catenin immunofluorescence labeling. Intracellular calcium, PKC and cAMP signaling were also investigated. All data was analyzed using SPSS. LD50 of TH was found to be 3.7% and concentrations ranging from 0.01%‐1% showed no cytotoxic effect to HUVEC. Induction with H2O2 was found to increase HUVEC permeability but the effect was significantly reversed by TH (p<0.05), of which the permeability inhibition peaked at 0.1%. TH also significantly (p<0.05) reduced the effect of H2O2 in vivo in all concentrations in a dose-dependent manner. Immunofluorescence confirmed that TH reduced stress fiber formation and the colocalization of caveolin-1 and β-catenin in HUVEC. TH also significantly (p<0.05) decreased intracellular calcium release and PKC activity, while maintained the level of cAMP when induced with H2O2. In conclusions, TH ameliorates H2O2‐induced endothelial hyperpermeability in vitro and in vivo via suppression of adherence junction protein re‐distribution, reduction of intracellular calcium and PKC activity while maintaining the cAMP production.